Tenth Five Year Plan, 2002-2007 and Annual Plan, 2002-2003 Planning Department, Government of Maharashtra - Planning Commission (Planning Commission, 2002)
The 10th Five Year Plan 2002-2007 and Annual Plan 2002-2003 are commencing in the background of economic slow down at one hand and adoption of policy of reforms in various sectors on the other. There is also disappointing progress in many important social as well as infrastructural sector. Therefore, it is an opportune time for us to modify our goals and priorities and to device new directions for our policies to survive in the rapidly changing economy of not only the country but also the World. Our human development indicators are not in tandem with our achievements in the industrial, social and infrastructure sectors. As 10th plan is first Five Year Plan of the new millennium, we must modify our policies and institutions based on the past experience.
Planning Department, Government of Maharashtra